A Comparison of the Onlay and Sublay Mesh Procedures for the Repair Of Ventral Hernias - Faryal Saeed, Kamran Khan, Sana Israr, Ajmal Khan, Ibrar Ahmed, Marium Khurshid (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study is to compare the outcomes of the on-lay mesh technique and the sub-lay mesh technique for ventral hernia repair. Study Design: Observational/ Retrospective Place & Duration: Benazir Bhutto Shaheed Hospital, Abbottabad; from May 2022-October-2022 Methods: 116 individuals of both sexes, aged 18 to 75, who were undergoing ventral hernia repair were examined. After receiving the patient’s consent, information about the patient’s age and gender was recorded. All of the patients were equally split into two groups, Group I and Group II. Participants in Group I were treated with an on-lay mesh method, while those in Group II were given a sub-lay approach. Consequences such as discomfort after surgery, bacterial infections, seroma development, and lengths of stay in the hospital were documented and compared between the two groups. All data was analyzed with SPSS 24. Results: In group I mean age was 47.12+5.38 years and in group II mean age was 48.7+11.66 years. Among all, majority of the cases 67 (57.8%) were females and 49 (42.2%) cases were males. Postoperative pain was significantly higher in the group I 5.1+3.18 whereas in the group II, it was lower 2.9+4.16, with wound infection affecting 10 (17.2%) patients vs 5 (5.2%) patients (P<0.005). Seroma was identified in 3 (5.2%) of Group II patients and 7 (12.1%) of Group I patients (p<0.005). Hospitalization durations were significantly longer for participants in Group I (6.0+1.36 days) compared to those in Group II (3.2+0.44 days; p<0.05). Conclusion: This research came to the conclusion that the sub-lay mesh approach for ventral hernia repair was not only successful but also safe, with a very low risk of problems when compared to the on-lay mesh operation. Keywords: On-lay Mesh Technique, Ventral Hernia Repair, Outcomes, Sub-lay Mesh Technique